2016
DOI: 10.1128/jvi.03220-14
|View full text |Cite
|
Sign up to set email alerts
|

Intricate Roles of Mammalian Sirtuins in Defense against Viral Pathogens

Abstract: For a number of years, sirtuin enzymes have been appreciated as effective "sensors" of the cellular environment to rapidly transmit information to diverse cellular pathways. Much effort was placed into exploring their roles in human cancers and aging. However, a growing body of literature brings these enzymes to the spotlight in the field of virology. Here, we discuss sirtuin functions in the context of viral infection, which provide regulatory points for therapeutic intervention against pathogens.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
54
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 50 publications
(54 citation statements)
references
References 21 publications
0
54
0
Order By: Relevance
“…Recent work demonstrated that addition of this compound to cell culture pre- and post- exposure to ZIKV reduced the viral load from 30% to 90%, respectively, showing another promising venue of sirtuins as viral inhibiting agents [ 102 ]. The bacterial sirtuin CobB, a homolog of Escherichia coli sirtuin negatively impacted the growth of both bacteriophages T4 and λ [ 103 , 104 ]. This all points to sirtuins as another area of study yet to be explored in the context of Wolbachia -mediated pathogen blocking.…”
Section: Discussionmentioning
confidence: 99%
“…Recent work demonstrated that addition of this compound to cell culture pre- and post- exposure to ZIKV reduced the viral load from 30% to 90%, respectively, showing another promising venue of sirtuins as viral inhibiting agents [ 102 ]. The bacterial sirtuin CobB, a homolog of Escherichia coli sirtuin negatively impacted the growth of both bacteriophages T4 and λ [ 103 , 104 ]. This all points to sirtuins as another area of study yet to be explored in the context of Wolbachia -mediated pathogen blocking.…”
Section: Discussionmentioning
confidence: 99%
“…Because neurons rely on intercellular signaling through synaptic vesicle formation and trafficking, it is tempting to speculate that SIRT2 association with these diseases is partly provided by its role in protein secretion and other membranebound trafficking pathways. SIRT2 impact on viral infection (11,90) might also be connected to intracellular trafficking. Viruses commonly use microtubule networks for capsid trafficking, genome delivery, and assembly (91).…”
Section: Fig 6 Sirt2 Impact On Protein Levels Of Membrane Traffickimentioning
confidence: 99%
“…Viruses have been known to appropriate Sirt regulatory pathways through the manipulation of host epigenetic and transcriptional changes (Budaveva et al, 2016). For example, Influenza A evolved to encode NS1 to mimic histone H3 and suppress antiviral genes; thus, Sirt inhibition increased Influenza A titers (Budaveva et al, 2016). Although, to our knowledge, there is no literature on how phages, would affect Sirt3, our findings suggest that phages may induce similar effects as that of a viral infection.…”
Section: Decreases Neuroprotectionmentioning
confidence: 71%
“…Sirt3 is a mitochondrial de-acetylate that influences almost every pathway in the mitochondria and plays a primary role in stress resistance, metabolism, neurodegenerative disease and aging (McDonnell et al, 2015;Ansari et al, 2017;Anamika, Khanna, Acharjee, Acharjee, & Trigun, 2017;Budaveva, Rowland & Cristea, 2016). Mitochondrial dysfunction is linked to aging due to being both a source and target of ROS (Kincaid & Bossy-Wetzel, 2013), Sirt3 can eliminate ROS and prevent apoptosis; hence, it is generally thought to be neuroprotective (McDonnell et al, 2015).…”
Section: Decreases Neuroprotectionmentioning
confidence: 99%
See 1 more Smart Citation